2015
DOI: 10.1016/j.eats.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic-Assisted Acromioclavicular Joint Reconstruction Using the TightRope Device With Allograft Augmentation: Surgical Technique

Abstract: Surgical management of acromioclavicular (AC) joint separations remains challenging, especially in the revision setting. Most commonly, Rockwood type I and II injuries are managed nonoperatively whereas type IV, V, and VI injuries are managed with surgery. Type III separations are more controversial, with evidence supporting both nonoperative and operative treatment options. Multiple different arthroscopic techniques have been described; however, there is no current gold standard. AC joint reconstruction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“… 42 On the other hand, the requirement of multiple drill holes in the clavicle can also create stress risers on bone that might result in implant cut-out. 43 Other complications are acromial osteolysis and fracture, AC joint osteoarthritis, subacromial impingement and rotator cuff tears. The need for a second surgery for implant removal is another disadvantage that might lead to late fracture of the distal clavicle after a low-energy trauma.…”
Section: Discussionmentioning
confidence: 99%
“… 42 On the other hand, the requirement of multiple drill holes in the clavicle can also create stress risers on bone that might result in implant cut-out. 43 Other complications are acromial osteolysis and fracture, AC joint osteoarthritis, subacromial impingement and rotator cuff tears. The need for a second surgery for implant removal is another disadvantage that might lead to late fracture of the distal clavicle after a low-energy trauma.…”
Section: Discussionmentioning
confidence: 99%
“…7 Our technique uses a tensioning device to reduce, in a controlled fashion, the superiorly migrated clavicle to the acromion. Prior techniques of manually forcing the clavicle inferiorly with an instrument while axially loading the arm superiorly to elevate the acromion 8 are imprecise and potentially dangerous because the instrument on the superior clavicle can easily slip and injure the neurovascular structures just underneath the clavicle.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, with the stress displacement gradually increased, the CC ligaments of the normal group first showed a fibrous tear and, finally, ruptured, while both of the techniques failed mainly because of tunnel fractures. Numerous studies have demonstrated that the strength of the suture button construct is better than that of the natural ligaments 13 . Chernchujit et al 27 reported the ultimate tensile strength of a two-anchor system with FiberWire No.…”
Section: Load Testingmentioning
confidence: 99%
“…On the basis of the Weaver–Dunn procedure, which uses the native AC ligament in AC joint reconstruction, there are many surgeries that can be performed to reconstruct the coracoclavicular (CC) ligament through tendon grafts or plate fixation 10,11 . The TightRope (TR) technique, involving two connected buttons and FiberWire sutures, is a common fixation surgery 12,13 . This technique prevents the CC ligament from separating and maintains the stability of the AC joint.…”
Section: Introductionmentioning
confidence: 99%